TRATAMENTO DA MASTITE BOVINA COM AMOXICILINA E ENROFLOXACINA BEM COMO COM A SUA ASSOCIAÇÃO - Langoni, H. [UNESP] (2024)
Mastitis is the generic name for inflammation of the mammary gland, no matter the cause, and it may be traumatic, toxic, allergic, metabolic or infectious, especially of bacterial origin. The process reduces milk production and changes the chemical composition of it, contributing to the decrease of its quality, turning into a possible problem for public health and for the dairy industry. The objective of this study was to evaluate the efficacy of bovine mastitis treatment using enrofloxacin and amoxicilin isolated or in association. Primiparous and multiparous cows in lactation were used, with subclinical mastitis diagnosed by CMT (+++ score), and others with clinical mastitis, diagnosed by positive black-bottom glass test. Microbiologic diagnostics was performed with 0.1 mL of each sample, in bovine blood-agar 10% and MacConkey agar, before and 21 days after the end of treatments in order to evaluate the microbiological recovery. Tests were performed to evaluate the sensitivity of each microorganism isolated to the drugs used in this study, and then the animals were treated by intramammary infusion after milking, in the morning and afternoon, during three consecutive days. The results obtained with the treatments with amoxicilin, enrofloxacin and the association of both drugs for the different microorganisms isolated (Staphylococcus epidermidis, Staphylococcus aureus, Streptococcus agalactiae and Escherichia coli), in both subclinical or clinical cases, independently of the involved microorganism, were respectively 84.6% and 75.0%; 83.3% and 75.0%; 87.5% and 84.0% % of recovery, demonstrating the viability of their use in the treatment of mastitis,e specially when used in association, and the process was caused by Streptococcus agalactiae and Escherichia coli.